Global versus local quantum correlations in the Grover search algorithm - Batle, J.; Raymond Ooi, C.H.; Farouk, A.; Alkhambashi, M.S.; Abdalla, S. (Springer Verlag (Germany), 2016)
Quantum correlations are thought to be the reason why certain quantum algorithms overcome their classical counterparts. Since the nature of this resource is still not fully understood, we shall investigate how entanglement and nonlocality among register qubits vary as the Grover search algorithm is run. We shall encounter pronounced differences between the measures employed as far as bipartite and global correlations are concerned.